2019
DOI: 10.3390/ma12050722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ions-Releasing Restorative Materials on the Dentine Bonding Longevity of Modern Universal Adhesives after Load-Cycle and Prolonged Artificial Saliva Aging

Abstract: This study aimed at evaluating the microtensile bond strength (MTBS) and fractographic features of dentine-bonded specimens created using universal adhesives applied in etch-and-rinse (ER) or self-etching (SE) mode in combination with modern ion-releasing resin-modified glass-ionomer cement (RMGIC)-based materials after load cycling and artificial saliva aging. Two universal adhesives (FTB: Futurabond M+, VOCO, Germany; SCU: Scotchbond Universal, 3M Oral Care, USA) were used. Composite build-ups were made with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
1
27
0
2
Order By: Relevance
“…(29) Dentin specimens bonded directly with ACITVA showed significantly low bond strength results at 24 h but durable on storage. As previously mentioned, (9) modern ion-releasing restorative materials might have the ability of preserving bonding performance of universal adhesives vulnerable to degradation over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(29) Dentin specimens bonded directly with ACITVA showed significantly low bond strength results at 24 h but durable on storage. As previously mentioned, (9) modern ion-releasing restorative materials might have the ability of preserving bonding performance of universal adhesives vulnerable to degradation over time.…”
Section: Discussionmentioning
confidence: 99%
“…All enamel groups after 6 months storage, whether bonded using adhesive system in etch and rinse mode, self-etch mode or directly bonded to ACITVA, showed stable bond strength which might be related to the bioactivity of ACITVA. Sauro et al, 2019 (9) reported that the use of modern ionreleasing restorative materials such as ACTIVA may preserve the bonding performance of those universal adhesives that are more prone to degradation after aging. ESEM images of enamel specimens bonded directly to ACTIVA demonstrated the formation of interlinking mesh of minerals at the interfacial gaps between enamel and ACITVA after 6 m storage ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluoroaluminum silicate particles and polyacid components undergo the acid-base setting reaction. 19 The smart material of Activa has the potential of releasing and recharging significant amounts of calcium, phosphate, and fluoride from the saliva or in the presence of a source like CPP-ACP paste, and therefore stimulates the apatite formation. This dynamic role acts against the marginal microleakage and discoloration of the restoration margin and improves the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%